Development and Characterization of Microsatellite Markers for Lilium longiflorum (Liliaceae) - Satomi Sakazono; Michikazu Hiramatsu; Masao Watanabe; Hiroshi Okubo (Applications in Plant Sciences, 2013)
Premise of the study: Ten microsatellite primers were developed to obtain information on genetic variation in Lilium longiflorum, a bulbous species showing high intraspecific genetic differentiation. Methods and Results: Of 61 microsatellite loci isolated using the dual suppression PCR technique, 10 loci were effective to characterize and estimate genetic variation in two populations of L. longiflorum. The number of alleles at each locus was different between the populations (averages = 3.2 and 10.3 alleles per locus), and the mean observed heterozygosity values were 0.245 and 0.732. Conclusions: Our results demonstrate that there is significant genetic variation between the populations and that the microsatellite markers developed in this study will be useful tools for the investigation of the genetic structure and mating system of natural L. longiflorum populations.